Modelling and Simulation: An Overview - Michael McAleer; Felix Chan; Les Oxley (Tinbergen Institute, 2013)
The papers in this special issue of Mathematics and Computers in Simulation cover the following topics: improving judgmental adjustment of model-based forecasts, whether forecast updates are progressive, on a constrained mixture vector autoregressive model, whether all estimators are born equal: the empirical properties of some estimators of long memory, characterising trader manipulation in a limit-order driven market, measuring bias in a term-structure model of commodity prices through the comparison of simultaneous and sequential estimation, modelling tail credit risk using transition matrices, evaluation of the DPC-based inclusive payment system in Japan for cataract operations by a new model, the matching of lead underwriters and issuing firms in the Japanese corporate bond market, stochastic life table forecasting: a time-simultaneous fan chart application, adaptive survey designs for sampling rare and clustered populations, income distribution inequality, globalization, and innovation: a general equilibrium simulation, whether exchange rates affect consumer prices: a comparative analysis for Australia, China and India, the impacts of exchange rates on Australia's domestic and outbound travel markets, clean development mechanism in China: regional distribution and prospects, design and implementation of a Web-based groundwater data management system, the impact of serial correlation on testing for structural change in binary choice model: Monte Carlo evidence, and coercive journal self citations, impact factor, journal influence and article influence.
urn:NBN:nl:ui:15-1765/40408
Keywords: C15; C63; E27; E37; E47; F37; F47; 330; Modelling; simulation; forecasting; time series models; trading; credit risk; empirical finance; health economics; sampling; groundwater systems; exchange rates; structural change; citations; Zeitreihenanalyse; Prognoseverfahren; Modellierung; Simulation; Schätzung; Währungsrisiko; Kreditrisiko; Australien; China; Indien